EVALUASI PROSES PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS PAKET B DI PKBM BINA KREASI KOTA PEKANBARU - Yulia Selnita; Daeng Ayub Natuna; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The formulation of the problem in this study is "How is the learning process of children with special needs package B in Pekanbaru City PKBM Creation". This research uses a descriptive case study research model with a qualitative approach which aims to find out how the learning process of children with special needs package B in PKBM Bina Kreasi Kota Pekanbaru. This study consists of one variable, namely evaluation with indicators, namely (1) Component input, (2) Product components (3) Components of results. the subject of this study were 3 informants. The technique of collecting data is by conducting observations, interviews and documentation. Based on observations, the researchers found data that the learning process of children with special needs package B in Pekanbaru's PKBM Bina Kreasi Kota was good but from the use of learning media and learning strategies for each child it needed to be explained because each child is different so the strategy must be different.Key Words: Characteristics, Learning Process, Children with Special Needs